If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 7 = 3x + 49 Reorder the terms: 7 + 5x = 3x + 49 Reorder the terms: 7 + 5x = 49 + 3x Solving 7 + 5x = 49 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 7 + 5x + -3x = 49 + 3x + -3x Combine like terms: 5x + -3x = 2x 7 + 2x = 49 + 3x + -3x Combine like terms: 3x + -3x = 0 7 + 2x = 49 + 0 7 + 2x = 49 Add '-7' to each side of the equation. 7 + -7 + 2x = 49 + -7 Combine like terms: 7 + -7 = 0 0 + 2x = 49 + -7 2x = 49 + -7 Combine like terms: 49 + -7 = 42 2x = 42 Divide each side by '2'. x = 21 Simplifying x = 21
| 2x+4x+60=180 | | 100c^2-120c+36=0 | | 6x-18=-126 | | (-1/3)2 | | 5x+60+10x=180 | | 8x+3=6y-8 | | 3(y-6)-5y=-8 | | 42sqrt(4*2/41xsqrt00.125*x | | 8y/2 | | 42sqrt(4*2/41xsqrt00.125 | | 6y-2=9+10y | | 12×10^7/4×10^4 | | 34=2(v+2)-8v | | cos(34)•20/x | | 5(y-2)/4=-4y | | 3(6x-9)-8=18x-35 | | 9x+1=9(x+4) | | e^1.2x=4/x | | 2n-1=-3n+9 | | 6x^2-21x-12/3x-4 | | 32=8x+4(x+2) | | 7+x-7=12 | | y=2.25x+29.25 | | 2x+x-68=0 | | f(x)=r(x-3) | | x^6-36y^2=0 | | |4-x/5|=10 | | p^2+20=-9p | | -12=3+5w | | (X+1)(x-1)=64 | | 3+2(5x-1)=2x+3(4-5x) | | 4x^2=-5x+21 |